Digital Transformation in Tourism Education: Cultivating Entrepreneurial Competencies in Indonesian Higher Education Institutions for Tourism - Indrianto, Agoes Tinus Lis; Christy Widyawati (Journal of Practice Learning and Educational Development, 2025)
Indonesia's tourism education is encountering considerable obstacles in advancing students' entrepreneurial competencies amidst digital revolution. This study seeks to evaluate the influence of digitalization on tourist education and to ascertain its efficacy as well as the challenges to its implementation. Utilizing a descriptive qualitative methodology, data were collected via interviews with scholars and industry professionals, as well as through observations and recording from tourist higher education institutions. The findings reveal that while several institutions have incorporated technology into education, deficiencies in infrastructure and teacher preparedness persist as significant barriers. The study indicates that a more systematic approach is necessary to incorporate technology efficiently, ensuring graduates remain competitive in the digital tourist sector. This research advances the creation of a more flexible and innovative technology-driven educational strategy.